Working conditions and effective supervision: Does it matter for engineering faculty job satisfaction. Issue 2 (April 2021) - Kakada, Praveen; Deshpande, YM
The purpose of this study is to examine the impact of supervisor support and working conditions on job satisfaction among teaching faculty in private engineering colleges. The study on job satisfaction has greater importance with the passage of time because of its nature and impact on the faculty and society. The researcher administered a standardized questionnaire on 180 individual respondents to collect the data. Respondents filled the items manually with their characteristics: age, gender, qualification, work experience, and their job position to check their level of significance with the job satisfaction. Descriptive statistics, correlation, and regression analysis were used for the data analysis. Based on the statistical findings, supervisor support and working conditions have a significant positive relationship with job satisfaction. These findings extend the theoretical understanding of supervisor support and work environment which enhance the faculty job satisfaction. Results also urge colleges and higher educational institutions to understand and to emphasize the importance of the work environment, which has an impact on faculty job satisfaction.